The Impact of Information Technology in Educational Counseling for High School Students - Phan, Thi Yen; Dang, Vinh (International Journal of Education, Teaching, and Social Sciences, 2025)
In the context of digital transformation, Information Technology (IT) is increasingly asserting its important role in innovating educational counseling activities for high school students. The article analyzes the benefits that IT brings, including improving access to information, personalizing counseling and remote support. Tools such as artificial intelligence (AI) and big data allow the construction of automated counseling systems, helping students receive advice that is appropriate to their interests, abilities and personal goals. In addition, IT also supports organizing online counseling sessions via platforms such as Zoom or Google Meet, bringing high efficiency to students in remote areas. The application of IT also helps students explore their interests and abilities through online multiple-choice tests, while increasing interaction with experts through forums and seminars. However, the article also points out challenges such as lack of digital skills, digital divide and risk of losing personal information security. To overcome this, it is necessary to invest in technology infrastructure, enhance digital skills training and develop safe and easy-to-use consulting platforms. IT not only changes the way of consulting but also facilitates high school students to access information and orient their future in an effective and comprehensive way.